Pengetahuan, Sikap dan Dukungan Sosial sebagai Aspek Pengelolaan Diri pada Pasien Hipertensi: Studi Cross-Sectional - Jumadi Kipli Sinaga; Victor Trismanjaya Hulu; Mafe Robbi Simanjuntak; Eka Lolita Eliyanti Pakpahan (Pusat riset dan Inovasi Nasional, 2025)
As a chronic disease, hypertension requires long-term management focused on patient fulfillment, where the active role of individuals in self-care contributes significantly to the prevention of complications and improving quality of life. This study aims to explore knowledge, attitudes, and social support regarding self-management in hypertensive patients. This study is a descriptive study with a cross-sectional design. The population of this study was all hypertensive patients who received treatment at the Pulo Brayan Community Health Center in Medan City in 2025. The study sample consisted of 216 people selected using a simple random sampling technique. Data collection was carried out by distributing questionnaires to hypertensive patients based on the variables of knowledge, attitudes, and social support. The data obtained were then analyzed descriptively. The results showed that 60.6% of respondents with hypertension had a poor level of knowledge regarding hypertension management, while 39.4% had good knowledge. 55.1% of respondents showed a positive attitude towards hypertension management, and 44.9% had a negative attitude. 57.9% of respondents received good social support, and 42.1% of respondents experienced poor social support. In conclusion, most respondents had poor knowledge regarding hypertension management. However, most respondents demonstrated positive attitudes and received good social support in implementing hypertension self-management.